Hubungan Faktor Individu Dan Pekerjaan Terhadap Keluhan Work-Related Musculoskeletal Disorders (WRMSDs) Pada Petugas Kebersihan - Yasmine Aulia Ramadhan; Dyah Wulan Sumekar rengganis Wardani; Ramadhana Komala; Khairunnisa Berawi (Malahayati Nursing Journal, 2025)
ABSTRACT Work-Related Musculoskeletal Disorders (WRMSDs) are complaints of muscles, fascia, nerves, tendons, joints, and spine related to exposure to risk factors in the workplace, such as sprains, pain, and inflammation. Cleaners are one of the jobs that often experience WRMSDs. WRMSDs complaints can be influenced by several main factors, namely individual factors and work factors. The purpose of this study was to determine the relationship between individual and work factors and WRMSDs complaints in cleaners at the University of Lampung. This study used a cross-sectional approach, conducted at the University of Lampung from July 2024 to January 2025. The subjects of the study were 130 cleaners. Data were collected through filling in personal data, exercise habit questionnaires and Nordic Body maps, and measuring work posters using the OWAS method. Bivariate analysis used the Spearman and Mann-Whitney tests. There is a relationship between gender (p = 0,05) and WRMSDs complaints, and there is a relationship between age (p 0,001 and r = 0,355), work duration (p = 0,001 and r = 0,283), work posture (p = 0,001 and r = 0,289), and WRMSDs complaints with a weak correlation strength and positive direction. There is a relationship between work period (p 0,001 and r = 0,400) and WRMSDs complaints with a moderate correlation level and a positive direction. There is a relationship between exercise habits (p = 0,009 and r = -0,299) with a weak correlation level and a negative direction. There is no relationship between BMI (p = 0,717) and WRMSDs complaints. Factors related to WRMSDs complaints are age, gender, exercise habits, work period, work duration, and work posture. Factors not related to WRMSDs complaints are BMI. Keywords: Musculoskeletal Disorders, Individual Factors, Occupational Factors  ABSTRAK Work-Related Musculoskeletal Disorders (WRMSDs) merupakan keluhan pada otot, fascia, saraf, tendon, sendi, dan tulang belakang yang terkait dengan paparan faktor risiko di tempat kerja, seperti terkilir ,nyeri dan inflamasi. Petugas kebersihan merupakan salah satu pekerjaan yang sering mengalami WRMSDs. Keluhan WRMSDs dapat dipengaruhi oleh beberapa faktor utama, yaitu faktor individu serta faktor pekerjaan. Tujuan penelitian ini adalah mengetahui hubungan antara faktor individu dan pekerjaan terhadap keluhan WRMSDs pada petugas kebersihan Universitas Lampung. Penelitian ini menggunakan pendekatan cross-sectional, dilakukan di Universitas Lampung pada bulan Juli 2024-Januari 2025. Subjek penelitian adalah 130 petugas kebersihan. Data dikumpulkan melalui pengisian data diri, kuesioner kebiasaan olahraga dan Nordic Body map, serta pengukuran poster kerja dengan metode OWAS. Analisis bivariat menggunakan uji Spearman dan Mann Whitney. Terdapat hubungan antara jenis kelamin (p = 0,05) dan keluhan WRMSDs, serta terdapat hubungan antara usia (p  0,001 dan r = 0,355), durasi kerja (p = 0,001 dan r=0,283),  postur kerja (p = 0,001 dan r = 0,289) dan keluhan WRMSDs dengan kekuatan korelasi lemah dan arah yang positif. Terdapat hubungan antara masa kerja (p  0,001 dan r = 0,400) dan keluhan WRMSDs dengan tingkat korelasi sedang dan arah yang positif. Terdapat hubungan antara kebiasaan olahraga (p = 0,009 dan r = -0,299) dengan tingkat korelasi lemah dan arah yang negatif. Tidak terdapat hubungan antara IMT (p = 0,717) dengan keluhan WRMSDs. Faktor yang berhubungan dengan keluhan WRMSDs adalah usia, jenis kelamin, kebiasaan olahraga, masa kerja, durasi kerja, serta postur kerja. Faktor yang tidak berhubungan dengan keluhan WRMSDs adalah IMT. Kata Kunci: Gangguan Muskuloskeletal, Faktor Indiviu, Faktor Pekerjaan